What Makes Difficult to Keep Learning Japanese? Demotivational Factors Affecting on Indonesian University Students - Yamashita, Junko (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2020)
Demotivation can negatively influence the learner’s attitudes and behaviors, and result in negative learning outcomes. This paper investigates factors contributing to demotivation in learning Japanese as a foreign language in Indonesia, and the relationship between demotivating factors and present proficiencies. A seventeen-item questionnaire was completed by 157 Indonesian university students. As the result of exploratory factor analysis, questionnaire items consequently grouped to four categories: Course difficulty, Speaking anxiety, Devalued learning, and Boredom.The validity of the four-factor structure was verified by the confirmatory factor analysis method. In addition, two-way ANOVA was performed to investigate the relationship between demotivational factors and proficiency level. As a result, statistically significant differences were found between Low and High groups in all the factors, and between Middle and High groups in the factors expect for Devalued learning. In addition, the scores of Speaking anxiety and Boredom consistently scored the highest among the four factors. However, the degree of demotivation was decreased as the learners’ Japanese proficiency improved. Findings from this study indicated that teachers should strive to make classes not only less anxious but also more interesting. Moreover, teachers should scaffold learners, especially low proficient beginners to prevent or minimize their demotivation.